2020
DOI: 10.1016/j.cgh.2019.09.041
|View full text |Cite
|
Sign up to set email alerts
|

How, When, and for Whom Should We Perform Therapeutic Drug Monitoring?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 80 publications
0
59
0
Order By: Relevance
“…Currently, no data exists to identify which patients are more likely to benefit from dose escalation, and management of attenuated response is based on clinical judgment. As for anti-TNF therapy, therapeutic drug monitoring with incorporation of pharmacokinetic data in developing a management algorithm for primary and secondary failure will likely become a A c c e p t e d M a n u s c r i p t mainstay of therapy, identifying appropriate patients needing a rescue dose (11)(12)(13). In the UNITI program, serum concentrations of ustekinumab were proportional to dose, and associated with clinical efficacy (1,14).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no data exists to identify which patients are more likely to benefit from dose escalation, and management of attenuated response is based on clinical judgment. As for anti-TNF therapy, therapeutic drug monitoring with incorporation of pharmacokinetic data in developing a management algorithm for primary and secondary failure will likely become a A c c e p t e d M a n u s c r i p t mainstay of therapy, identifying appropriate patients needing a rescue dose (11)(12)(13). In the UNITI program, serum concentrations of ustekinumab were proportional to dose, and associated with clinical efficacy (1,14).…”
Section: Discussionmentioning
confidence: 99%
“…The second is entitled "proactive" TDM, in which the quantification drug levels and/or antibodies is performed before failure, in all patients, allowing therapeutic adjustments to prevent both primary and secondary nonresponses. 32 Currently, the use of reactive TDM may be of benefit as www.irjournal.org compared to empirical change of therapy, owing to a reduction in the duration of an ineffective therapy, lower overall costs and to an increase in quality of life after therapeutic adjustment, drug levels and endoscopic remission. 33,34 There is still some uncertainty about the proper use of proactive TDM, once prospective trials comparing empirical or reactive changes in therapy demonstrated conflicting results.…”
Section: Tdm In Ibd: Concepts and Applicationsmentioning
confidence: 99%
“…The seminal extension study (IM-UNITI) ( 48 ) suggested 12-weekly maintenance dosing in biologic naive patients and 8-weekly dosing in anti-TNF therapy-experienced patients. Other ongoing trials include STARDUST (treat-to-target vs. routine case management in CD patients on UST), POWER (efficacy and safety of UST reinduction therapy in patients with moderate and severe CD), and RESCUE (loss of response to UST treated with dose escalation), which might help in guiding formulation of desired TLs for different therapeutic endpoints ( 49 ).…”
Section: Methodsmentioning
confidence: 99%